NK Cell Activity and CD57+/NKG2Chigh Phenotype Are Increased in Men Who Have Sex With Men at High Risk for HIV - Flórez-Álvarez, Lizdany; Blanquiceth, Yurany; Ramírez, Katherin; Ossa-Giraldo, Ana Claudia; Velilla, Paula A.; Hernandez, Juan C.; Zapata, Wildeman (Frontiers in Immunology, 2020)
Introduction: The HIV-exposed seronegative (HESN) status is for individuals who remain seronegative despite repeated exposure to HIV. One of the main cohorts within this group is men who have sex with men (MSM). Studies of this cohort have revealed different immunological and genetic mechanisms that can explain the phenomenon of natural HIV resistance. NK cells’ higher effector capacity is related to natural resistance to HIV. Besides, a new population of NK cells with adaptive features was described recently. These cells are increased in some HESN cohorts and appear to be involved in better control of viral replication in primarily HIV-infected subjects. The present study evaluated the role of NK cells in the natural resistance to HIV-1 infection in MSM. Methodology: Phenotypic and functional features were evaluated in NK cells from two groups of MSM, at different risks of HIV infection, according to the number of sexual partners. The production of IFN-γ and β-chemokines was included in the analysis, as well as the cytotoxic capacity and adaptive NK cell frequency. Genetic features, such as HLA and KIR allele frequencies, were also explored. Results: High-risk MSM exhibit an increased frequency of fully mature and CD57+/NKG2Chigh NK cells. These individuals also show higher cytotoxic capacity and IFN-γ production in response to K562 stimuli. NK cells with a CD107a+/IFN-ɣ+ functional profile were found more frequently and displayed higher IFN-γ production capacity among high-risk MSM than among low-risk MSM. The protective allele HLA-B*18 was only present in the high-risk MSM group as well as HLA-B* 39. The protective phenotype KIR3DL1/S1-HLA-B*Bw4, in a homozygous state, was particularly abundant in the high-risk population. Notably, some of these functional features were related to higher frequencies of mature and CD57+/NKG2Chigh NK cells, which, in turn, were associated with a higher number of sexual partners. Conclusion: The changes observed in the NK cell compartment can be driven by the magnitude of sexual exposure and immunological challenges of high-risk individuals, which could influence their resistance/susceptibility to HIV infection.